Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

Detection, isolation, and identification of Rhizoctonia theobromae associated with cassava witches’ broom disease in the Philippines - Darwin M. Landicho; Ray Jerome M. Montañez; Vicky S. Manayon; Ma Kristina Yzabelle C. Sendaydiego; Jestoni O. Gaylo; Amor C. Dimayacyac; Ikuo Sato; Daigo Takemoto; Marita S. Pinili; Sotaro Chiba (Physiological and Molecular Plant Pathology, 2025)

Effect of the garlic matrix and inclusion level on in vitro methane production and fermentation - N.F. Sari; S. Stergiadis; P.P. Ray; C. Rymer; L.A. Crompton; K.E. Kliem (Animal Feed Science and Technology, 2025)

Complete mitochondrial DNA genome of the Indian Chhattisgarh duck and its phylogenetic analysis - Rajni Kumari; Ratna Prabha; Tirupati Rao Golla; P. K. Ray; Reena Kamal; Jaipal S. Choudhary; Abhay Kumar; Sanjay Kumar; Shanker Dayal; P. C. Chandran; Jyoti Kumar; M. K. Tripathi; et al. (Journal of Genetics, 2025)

Socio-economic impacts and responses of the fishing industry and fishery managers to changes in small pelagic fish distribution and abundance - Felipe J. Quezada-Escalona; Desiree Tommasi; Isaac C. Kaplan; Pierre-Yves Hernvann; Timothy H. Frawley; Dorleta Garcia; Leire Ibaibarriaga; Sonia Sánchez-Maroño; Carryn de Moor; Jennifer Beckensteiner; Amy M. Schueller; Diana Feijó; et al. (Reviews in Fish Biology and Fisheries, 2025)
Small Pelagic Fish (SPF) exhibit large fluctuations in abundance and distribution in response to environmental variability. To maintain the resilience of fishing communities and develop effective and equitable climate adaptation strategies, improved understanding of how the fishing industry responds to spatio-temporal shifts within and across SPF populations is of critical importance. In this paper, we examine the responses of the fishing industry and resource managers to shifts in SPF availability worldwide and identify the resulting socioeconomic impacts. Leveraging SPF case studies from around the globe, we synthesize and compare the social-ecological linkages and feedbacks mediating how SPF fisheries respond to changes in marine ecosystem structure and function associated with (1) spatial shifts in species distribution and habitat availability, (2) ‘boom and bust’ population dynamics, or (3) changes in fish size and quality. Our case studies illustrate multiple paths towards the resilience of small pelagic fisheries and the fishing industry dependent upon them while emphasizing the need for increased coordination and cooperation across sectors and scales as climate change progresses. Drawing from the lessons offered by historical responses, as environmental variability increases, efforts to increase the flexibility and dynamism of SPF harvest portfolios and management strategies, licensing regimes, and international catch and allocation agreements may be required to ensure resource sustainability and human well-being.

Retraction Note: Transgenic rice expressing Allium sativum leaf lectin with enhanced resistance against sap-sucking insect pests - Prasenjit Saha; Pralay Majumder; Indrajit Dutta; Tui Ray; S. C. Roy; Sampa Das (Planta, 2025)

Electrocatalytic synergies of melt-quenched Ni-Sn-Se-Te nanoalloy for direct seawater electrolysis - John D. Rodney; Sindhur Joshi; Subhasmita Ray; Lavanya Rao; S. Deepapriya; Karel Carva; Badekai Ramachandra Bhat; N.K. Udayashankar; Suresh Perumal; Sadhana Katlakunta; C. Justin Raj; Byung Chul Kim (Chemical Engineering Journal, 2024)

Effects of increasing soil moisture on Antarctic desert microbial ecosystems - Eden Zhang; Sin Yin Wong; Paul Czechowski; Aleks Terauds; Angelique E. Ray; Nicole Benaud; Devan S. Chelliah; Daniel Wilkins; Kate Montgomery; Belinda C. Ferrari (Conservation Biology, 2024)
Overgeneralization and a lack of baseline data for microorganisms in high‐latitude environments have restricted the understanding of the microbial response to climate change, which is needed to establish Antarctic conservation frameworks. To bridge this gap, we examined over 17,000 sequence variants of bacteria and microeukarya across the hyperarid Vestfold Hills and Windmill Islands regions of eastern Antarctica. Using an extended gradient forest model, we quantified multispecies response to variations along 79 edaphic gradients to explore the effects of change and wind‐driven dispersal on community dynamics under projected warming trends. We also analyzed a second set of soil community data from the Windmill Islands to test our predictions of major environmental tipping points. Soil moisture was the most robust predictor for shaping the regional soil microbiome; the highest rates of compositional turnover occurred at 10–12% soil moisture threshold for photoautotrophs, such as Cyanobacteria , Chlorophyta , and Ochrophyta . Dust profiles revealed a high dispersal propensity for Chlamydomonas , a microalga, and higher biomass was detected at trafficked research stations. This could signal the potential for algal blooms and increased nonendemic species dispersal as human activities increase in the region. Predicted increases in moisture availability on the Windmill Islands were accompanied by high photoautotroph abundances. Abundances of rare oligotrophic taxa, such as Eremiobacterota and Candidatus Dormibacterota, which play a crucial role in atmospheric chemosynthesis, declined over time. That photosynthetic taxa increased as soil moisture increased under a warming scenario suggests the potential for competition between primary production strategies and thus a more biotically driven ecosystem should the climate become milder. Better understanding of environmental triggers will aid conservation efforts, and it is crucial that long‐term monitoring of our study sites be established for the protection of Antarctic desert ecosystems. Furthermore, the successful implementation of an improved gradient forest model presents an exciting opportunity to broaden its use on microbial systems globally.

Editorial Expression of Concern: Transgenic rice expressing Allium sativum leaf lectin with enhanced resistance against sap-sucking insect pests - Prasenjit Saha; Pralay Majumder; Indrajit Dutta; Tui Ray; S. C. Roy; Sampa Das (Planta, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

The development of early farming diets and population change in the Maya region and their climate context - Erin E. Ray; Nadia C. Neff; Paige Lynch; Jose Mes; Matthew S. Lachniet; Douglas J. Kennett; Keith M. Prufer (Quaternary International, 2024)

Analysis of localized features during wet and dry rainfall episodes over southern tip of India - E. A. Resmi; B. Preethi; R. S. Ajayamohan; Pallav Ray; C. K. Unnikrishnan; S. Nita; R. K. Sumesh; J. Dharmadas (International Journal of Climatology, 2023)
The large spatial and temporal variability of wet and dry spells of the Indian Summer Monsoon (ISM) poses the great challenge in understanding and predicting monsoonal rainfall. This challenge is further exacerbated over smaller regions, such as the southern tip of India, which receives the first spell of ISM rainfall. In this study, the characteristic features and possible precursors for wet and dry spells of rainfall over the southern tip of India are investigated. We also explore the variability in monsoon low‐level jet (LLJ) in relation to wet and dry spells over a coastal station Thiruvananthapuram (8.48°N, 76.95°E) in southwest India using in situ observations and other ancillary datasets. The results show that a wet spell spanning 3–4 days contributes about 30% of seasonal rainfall. Wet spells are characterized by westerly wind anomaly in the southern tip of India and easterly wind anomaly in northern India, leading to anomalous cyclonic vorticity over the Indian subcontinent. The opposite happens during dry spells. These characteristics are prominent from 2 days prior to the initiation of the spells, suggesting they may be used as precursors for forecasting wet and dry spells over Thiruvananthapuram. Analysis of low‐ to mid‐tropospheric (2 and 4 km) humidity reveals significant moistening (drying) during wet (dry) spells. Yet, both wet and dry spells experience humid (>80%) boundary layer. The differences in mid‐level humidity and thermodynamical structures between wet and dry spells seem to contribute to distinct rainfall characteristics over the southern tip of India. These results indicate that the use of in situ observations along with large‐scale reanalysis datasets may provide valuable information on the precursors for wet and dry spells over the southern tip of India, which can help both in regional‐ and city‐level planning and management of water resources.

Impact of relative humidity and temperature oscillations mimicking authentic storage during shipping on whey proteins powders properties - J. Burgain; G. Francius; L. Cvetkovska; C. Paris; M. Alexander; C. Ray; S. El-Kirat-Chatel; C. Gaiani (Food Structure, 2023)

Cytogenetic Diversity in Scilloideae (Asparagaceae): a Comprehensive Recollection and Exploration of Karyo-Evolutionary Trends - Sayantani Nath; Sayantika Sarkar; Sayali D. Patil; Partha Sarathi Saha; Manoj M. Lekhak; Sudipta Ray; Satyawada Rama Rao; S. R. Yadav; R. C. Verma; Manoj K. Dhar; S. N. Raina; Sumita Jha (The Botanical Review, 2023)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Breeding latitude is associated with the timing of nesting and migration around the annual calendar among Purple Martin (Progne subis) populations - L. R. Neufeld; S. Muthukumarana; J. D. Fischer; J. D. Ray; J. Siegrist; K. C. Fraser (Journal of Ornithology, 2021)

Cancer mortality risk, fine particulate air pollution, and smoking in a large, representative cohort of US adults - Nathan C. Coleman; Richard T. Burnett; Joshua D. Higbee; Jacob S. Lefler; Ray M. Merrill; Majid Ezzati; Julian D. Marshall; Sun-Young Kim; Matthew Bechle; Allen L. Robinson; C. Arden Pope (Cancer Causes & Control, 2020)

Identification of quantitative trait loci for carbon isotope ratio (δ13C) in a recombinant inbred population of soybean - Sumandeep K. Bazzer; Avjinder S. Kaler; Jeffery D. Ray; James R. Smith; Felix B. Fritschi; Larry C. Purcell (Theoretical and Applied Genetics, 2020)

Choosing best practices for managing impacts of trawl fishing on seabed habitats and biota - Robert A. McConnaughey; Jan G. Hiddink; Simon Jennings; C. Roland Pitcher; Michel J. Kaiser; Petri Suuronen; Marija Sciberras; Adriaan D. Rijnsdorp; Jeremy S. Collie; Tessa Mazor; Ricardo O Amoroso; Ana M. Parma; et al. (Fish and Fisheries, 2020)
Bottom trawling accounts for almost one quarter of global fish landings but may also have significant and unwanted impacts on seabed habitats and biota. Management measures and voluntary industry actions can reduce these impacts, helping to meet sustainability objectives for fisheries, conservation and environmental management. These include changes in gear design and operation of trawls, spatial controls, impact quotas and effort controls. We review nine different measures and actions and use published studies and a simple conceptual model to evaluate and compare their performance. The risks and benefits of these management measures depend on the extent to which the fishery is already achieving management objectives for target stocks and the characteristics of the management system that is already in place. We offer guidance on identifying best practices for trawl‐fisheries management and show that best practices and their likelihood of reducing trawling impacts depend on local, national and regional management objectives and priorities, societal values and resources for implementation. There is no universal best practice, and multiple management measures and industry actions are required to meet sustainability objectives and improve trade‐offs between food production and environmental protection.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Diversity of hepatitis C virus infection among HIV-infected people who inject drugs in India - S. S. Solomon; D. Boon; S. Saravanan; A. K. Srikrishnan; C. K. Vasudevan; P. Balakrishnan; D. Persaud; S. C. Ray; S. Mehta; S. H. Mehta (VirusDisease, 2019)

Association mapping identifies loci for canopy temperature under drought in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; Antonio R. Asebedo; C. Andy King; E. E. Gbur; Larry C. Purcell (Euphytica, 2018)

Response of benthic fauna to experimental bottom fishing: A global meta‐analysis - Marija Sciberras; Jan Geert Hiddink; Simon Jennings; Claire L Szostek; Kathryn M Hughes; Brian Kneafsey; Leo J Clarke; Nick Ellis; Adriaan D Rijnsdorp; Robert A McConnaughey; Ray Hilborn; Jeremy S Collie; et al. (Fish and Fisheries, 2018)
Bottom‐contact fishing gears are globally the most widespread anthropogenic sources of direct disturbance to the seabed and associated biota. Managing these fishing disturbances requires quantification of gear impacts on biota and the rate of recovery following disturbance. We undertook a systematic review and meta‐analysis of 122 experiments on the effects‐of‐bottom fishing to quantify the removal of benthos in the path of the fishing gear and to estimate rates of recovery following disturbance. A gear pass reduced benthic invertebrate abundance by 26% and species richness by 19%. The effect was strongly gear‐specific, with gears that penetrate deeper into the sediment having a significantly larger impact than those that penetrate less. Sediment composition (% mud and presence of biogenic habitat) and the history of fishing disturbance prior to an experimental fishing event were also important predictors of depletion, with communities in areas that were not previously fished, predominantly muddy or biogenic habitats being more strongly affected by fishing. Sessile and low mobility biota with longer life‐spans such as sponges, soft corals and bivalves took much longer to recover after fishing (>3 year) than mobile biota with shorter life‐spans such as polychaetes and malacostracans (

Phosphorus Budget of the Sundarban Mangrove Ecosystem: Box Model Approach - R. Ray; N. Majumder; C. Chowdhury; S. Das; T. K. Jana (Estuaries and Coasts, 2018)

Genome-wide association mapping of canopy wilting in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; C. Andy King; Larry C. Purcell (Theoretical and Applied Genetics, 2017)

The future of nemertean taxonomy (phylum Nemertea) — a proposal - Per Sundberg; Sónia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Jörn von Döhren; Daria Krämer; Ray Gibson; Gonzalo Giribet; Alfonso Herrera‐Bachiller; Juan Junoy; Hiroshi Kajihara; Sebastian Kvist; et al. (Zoologica Scripta, 2016)

Metabarcoding and metabolome analyses of copepod grazing reveal feeding preference and linkage to metabolite classes in dynamic microbial plankton communities - Jessica L. Ray; Julia Althammer; Katrine S. Skaar; Paolo Simonelli; Aud Larsen; Diane Stoecker; Andrey Sazhin; Umer Z. Ijaz; Christopher Quince; Jens C. Nejstgaard; Marc Frischer; Georg Pohnert; et al. (Molecular Ecology, 2016)
In order to characterize copepod feeding in relation to microbial plankton community dynamics, we combined metabarcoding and metabolome analyses during a 22‐day seawater mesocosm experiment. Nutrient amendment of mesocosms promoted the development of haptophyte ( Phaeocystis pouchetii )‐ and diatom ( Skeletonema marinoi )‐dominated plankton communities in mesocosms, in which Calanus sp. copepods were incubated for 24 h in flow‐through chambers to allow access to prey particles ( P. pouchetii , were passively consumed or even negatively selected according to our indicator. Our analysis of the relationship between Calanus grazing ratios and intracellular metabolite profiles indicates the importance of carbohydrates and lipids in plankton succession and copepod–prey interactions. This molecular characterization of Calanus sp. grazing therefore provides new evidence for selective feeding in mixed plankton assemblages and corroborates previous findings that copepod grazing may be coupled to the developmental and metabolic stage of the entire prey community rather than to individual prey abundances.

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Real‐time spatial management approaches to reduce bycatch and discards: experiences from Europe and the United States - Alyson S Little; Coby L Needle; Ray Hilborn; Daniel S Holland; C Tara Marshall (Fish and Fisheries, 2015)
Spatial management measures are currently being used to manage bycatch and discards, given the spatial heterogeneity of fish distributions. However, permanent fishing closures are often poorly implemented, unresponsive to stock dynamics and do not achieve their management objectives. Recently, real‐time spatial management tools for managing bycatch and discards implemented under either a comanagement or self‐governance approach have been introduced in Europe and the US . Real‐time catch and discard information is shared among fishers to incentivise and encourage vessels to leave areas of high bycatch. Here, the similarities and differences, in governance, implementation and management of ten real‐time spatial management systems from across Europe and the US are reviewed. A framework is developed to characterize the attributes associated with voluntary, private and regulatory real‐time spatial management tools. Challenges and management practices in the different case studies are reviewed providing insights for designing these spatial management tools. The results illustrate that real‐time spatial management approaches can create incentives for fishers to develop, use and share information and technology to avoid undesired catch. Compared with Europe, the US has developed spatial management tools with more truly real‐time mechanisms and with greater involvement of the fishing industry in designing and operating the tools.

Peralkaline felsic magmatism at the Nemrut volcano, Turkey: impact of volcanism on the evolution of Lake Van (Anatolia) IV - Ray Macdonald; Mari Sumita; Hans-Ulrich Schmincke; Bogusław Bagiński; John C. White; Sławomir S. Ilnicki (Contributions to Mineralogy and Petrology, 2015)

Geochemistry of PGE in mafic rocks of east Khasi Hills, Shillong Plateau, NE India - Sampa Hazra; Jyotisankar Ray; C Manikyamba; Abhishek Saha; S S Sawant (Journal of Earth System Science, 2015)

Assessment of organochlorine pesticide residues in Indian flue-cured tobacco with gas chromatography-single quadrupole mass spectrometer - Rakesh Kumar Ghosh; Zareen S. Khan; C. V. N. Rao; Kaushik Banerjee; D. Damodar Reddy; T. G. K. Murthy; Nalli Johnson; Deb Prasad Ray (Environmental Monitoring and Assessment, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Occupancy patterns of large mammals in the Far North of Ontario under imperfect detection and spatial autocorrelation - Lucy G. Poley; Bruce A. Pond; James A. Schaefer; Glen S. Brown; Justina C. Ray; Devin S. Johnson (Journal of Biogeography, 2014)
Aim An understanding of the factors that influence species distributions in heterogeneous landscapes is important when making decisions regarding conservation. Moreover, occupancy probabilities based on detection data can reveal important species–habitat relationships. Accounting for the spatial autocorrelation of detection data increases the statistical validity of occupancy models, but is not often considered. Using novel occupancy modelling that explicitly incorporates detectability and spatial autocorrelation, we assessed the influence of habitat on occupancy patterns of woodland caribou ( Rangifer tarandus caribou ), moose ( Alces alces ) and wolves ( Canis lupus ) across a broad biogeographical extent where fire is the dominant agent of disturbance. Location Northern Ontario, Canada. Methods We aerially surveyed 3851 sampling units, each covering 100 km 2 , for woodland caribou, moose and wolves in February–March in 2009, 2010 and 2011, and visited 1663 units more than once to estimate detectability. We used restricted spatial regression to model occupancy probabilities of each species with respect to habitat factors in two ecozones, accounting for both imperfect detection and lack of independence of sampling units. Results Covariates influencing species detection varied among ecozones and species. Caribou occupancy was positively related to bogs and negatively related to disturbed areas, while moose occupancy showed opposite responses to these covariates. Wolf occupancy was related to high prey occupancy. Explicitly accounting for spatial autocorrelation in detection data reduced the chance of type I error in occupancy estimates compared with non‐spatial models. Main conclusions Habitat relationships and occupancy patterns support the hypothesis that caribou remain spatially segregated from moose to reduce predation risk. The broad scale of analysis indicated changes in species–habitat relationships, suggesting that limiting factors vary across biogeographical gradients. The spatial pattern in caribou occupancy allowed us to identify important areas used by caribou across the region, including the ecotone between fire‐driven boreal forests and peatland complexes. The evidence for significant relationships between caribou and land cover, predators and alternate prey underscores the need for careful planning of development and infrastructure in the area.

Comparative pharmacokinetics of PAMAM-OH dendrimers and HPMA copolymers in ovarian tumor-bearing mice - S. Sadekar; O. Linares; G. J. Noh; D. Hubbard; A. Ray; M. Janát-Amsbury; C. M. Peterson; J. Facelli; H. Ghandehari (Drug Delivery and Translational Research, 2013)

Implication of Organic Matter on Arsenic and Antimony Sequestration in Sediment: Evidence from Sundarban Mangrove Forest, India - S. K. Mandal; R. Ray; C. Chowdhury; N. Majumder; T. K. Jana (Bulletin of Environmental Contamination and Toxicology, 2013)

Spatial occupancy models for large data sets - Devin S. Johnson; Paul B. Conn; Mevin B. Hooten; Justina C. Ray; Bruce A. Pond (Ecology, 2013)
Since its development, occupancy modeling has become a popular and useful tool for ecologists wishing to learn about the dynamics of species occurrence over time and space. Such models require presence–absence data to be collected at spatially indexed survey units. However, only recently have researchers recognized the need to correct for spatially induced overdisperison by explicitly accounting for spatial autocorrelation in occupancy probability. Previous efforts to incorporate such autocorrelation have largely focused on logit‐normal formulations for occupancy, with spatial autocorrelation induced by a random effect within a hierarchical modeling framework. Although useful, computational time generally limits such an approach to relatively small data sets, and there are often problems with algorithm instability, yielding unsatisfactory results. Further, recent research has revealed a hidden form of multicollinearity in such applications, which may lead to parameter bias if not explicitly addressed. Combining several techniques, we present a unifying hierarchical spatial occupancy model specification that is particularly effective over large spatial extents. This approach employs a probit mixture framework for occupancy and can easily accommodate a reduced‐dimensional spatial process to resolve issues with multicollinearity and spatial confounding while improving algorithm convergence. Using open‐source software, we demonstrate this new model specification using a case study involving occupancy of caribou ( Rangifer tarandus ) over a set of 1080 survey units spanning a large contiguous region (108 000 km 2 ) in northern Ontario, Canada. Overall, the combination of a more efficient specification and open‐source software allows for a facile and stable implementation of spatial occupancy models for large data sets.

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Particle Size Distribution of Ambient Aerosols in an Industrial Area - B. Padma Rao; A. Srivastava; F. Yasmin; S. Ray; N. Gupta; C. Chauhan; C. V. C. Rao; S. R. Wate (Bulletin of Environmental Contamination and Toxicology, 2012)

A Spatial Database of Cropping System and its Characteristics to Aid Climate Change Impact Assessment Studies - Sushma Panigrahy; Shibendu Shankar Ray; K. R. Manjunath; P. S. Pandey; S. K. Sharma; Anil Sood; Manoj Yadav; P. C. Gupta; N. Kundu; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

VEGF-C differentially regulates VEGF-A expression in ocular and cancer cells; promotes angiogenesis via RhoA mediated pathway - Bharat Kumar; Shailaja A. Chile; Kriti B. Ray; G. E. C. Vidyadhar Reddy; Murali K. Addepalli; A. S. Manoj Kumar; Venkata Ramana; Vikram Rajagopal (Angiogenesis, 2011)

Major ash eruptions of Barren Island volcano (Andaman Sea) during the past 72 kyr: clues from a sediment core record - Neeraj Awasthi; Jyotiranjan S. Ray; Amzad H. Laskar; Alok Kumar; M. Sudhakar; Rajneesh Bhutani; Hetu C. Sheth; Madhusudan G. Yadava (Bulletin of Volcanology, 2010)

Feasibility Evaluation of Pressurized Irrigation in Canal Commands - Ramesh C. Srivastava; Sheelabhadra Mohanty; Ramlal B. Singandhuppe; Rajiv K. Mohanty; Madhu S. Behera; Lala I. P. Ray; Deepika Sahoo (Water Resources Management, 2010)

Volcanology and eruptive styles of Barren Island: an active mafic stratovolcano in the Andaman Sea, NE Indian Ocean - Hetu C. Sheth; Jyotiranjan S. Ray; Rajneesh Bhutani; Alok Kumar; R. S. Smitha (Bulletin of Volcanology, 2009)

Geology and geochemistry of Pachmarhi dykes and sills, Satpura Gondwana Basin, central India: problems of dyke-sill-flow correlations in the Deccan Traps - Hetu C. Sheth; Jyotiranjan S. Ray; Ranjini Ray; Loÿc Vanderkluysen; John J. Mahoney; Alok Kumar; Anil D. Shukla; Partha Das; Subhrashis Adhikari; Bikashkali Jana (Contributions to Mineralogy and Petrology, 2009)

Biocontrol Efficacy of Bacillus subtilis Strains Isolated from Cow Dung Against Postharvest Yam (Dioscorea rotundata L.) Pathogens - M. R. Swain; R. C. Ray; C. S. Nautiyal (Current Microbiology, 2008)

Characterization of the complete genome of influenza A (H5N1) virus isolated during the 2006 outbreak in poultry in India - Koninika Ray; Varsha A. Potdar; Sarah S. Cherian; Shailesh D. Pawar; Santosh M. Jadhav; Shamal R. Waregaonkar; Anshu A. Joshi; Akhilesh C. Mishra (Virus Genes, 2008)

The role of medial prefrontal cortex in context-specific inhibition during reversal learning of a visual discrimination - R. J. McDonald; N. Foong; C. Ray; Z. Rizos; N. S. Hong (Experimental Brain Research, 2007)

Mapping of fault rupture of the 28 may 2004 iran earthquake (mw= 6.2) using satellite image - M. Sharifikia; C. S. Dubey; B. K. Sharma; M. Chaudhry; P. K. Champati Ray (Journal of the Indian Society of Remote Sensing, 2006)

RBx 7796: A novel inhibitor of 5-lipoxygenase - R. K. Shirumalla; K. S. Naruganahalli; S. G. Dastidar; V. Sattigeri; G. Kaur; C. Deb; J. B. Gupta; M. Salman; A. Ray (Inflammation Research, 2006)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

RETRACTED ARTICLE: Transgenic rice expressing Allium sativum leaf lectin with enhanced resistance against sap-sucking insect pests - Prasenjit Saha; Pralay Majumder; Indrajit Dutta; Tui Ray; S. C. Roy; Sampa Das (Planta, 2006)

Acetylcholinesterase activities in marine snail (Cronia contracta) as a biomarker of neurotoxic contaminants along the Goa coast, West coast of India - D. Gaitonde; A. Sarkar; S. Kaisary; C. D. Silva; C. Dias; D. P. Rao; D. Ray; R. Nagarajan; S. N. De Sousa; Subhodeep Sarker; D. Patill (Ecotoxicology, 2006)

Preface - Jyotiranjan S Ray; C Chakraborty (Journal of Earth System Science, 2006)

Water quality assessment of Gautami — Godavari mangrove estuarine ecosystem of Andhra Pradesh, India during September 2001 - S. C. Tripathy; A. K. Ray; S. Patra; V. V. Sarma (Journal of Earth System Science, 2005)

DDT and HCH Residues in Basmati Rice (Oryza sativa) Cultivated in Dehradun (India) - G. Suresh Babu; M. Farooq; R. S. Ray; P. C. Joshi; P. N. Viswanathan; R. K. Hans (Water, Air, & Soil Pollution, 2003)

Non-litter effects of elevated CO2 on forest floor microarthropod abundances - Randi A. Hansen; Ray S. Williams; David C. Degenhardt; David E. Lincoln (Plant and Soil, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Interaction of the non-protein-coding developmental and stress-induciblehsrω gene withRas genes ofDrosophila melanogaster - Pritha Ray; S C Lakhotia (Journal of Biosciences, 1998)

Integrated measures of ambient toxicity and fish community diversity in Chesapeake Bay tributaries - S. Ian Hartwell; Celia E. Dawson; Eric Q. Durell; Ray W. Alden; Peter C. Adolphson; David A. Wright; Gina M. Coelho; John A. Magee (Ecotoxicology, 1998)

Spike detection in biomedical signals using midprediction filter - S. Dandapat; G. C. Ray (Medical & Biological Engineering & Computing, 1997)

Effect of a growth hormone treatment on bone orthotropic elasticity in dwarf rats - Sean S. Kohles; Daniel A. Martinez; James R. Bowers; Arthur C. Vailas; Ray Vanderby (Annals of Biomedical Engineering, 1997)

Suppressive effect of quinalphos on the activity of accessory sex glands and plasma concentrations of gonadotrophins and testosterone in rats - A. Ray; S. Chatterjee; S. Ghosh; S. N. Kabir; A. Pakrashi; C. Deb (Archives of Environmental Contamination and Toxicology, 1991)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)